If my heart could talk : a story of family, faith, and miracles - Osteen, Dodie; Osteen, Joel (New York : FaithWords, 2016)
"Dodie Osteen, mother of Joel Osteen, gives readers a personal account of her extraordinary life and shares what she has learned about love, faith, and family,"--Amazon.com.
Includes bibliographical references.
Keywords: Osteen, Dodie; Osteen, Dodie -- Family; Lakewood Church (Houston, Tex.) -- History; Christian women -- Biography; Autobiographies